PENGARUH KOMBINASI BASIS PEG 400 DAN BASIS PEG 4000 DALAM FORMULASI SALEP EKSTRAK DAUN SUKUN (Artocarpus altilis) TERHADAP AKTIVITAS ANTIBAKTERINYA - Sella_Arbi Nur_Ullya Dewi; Dewi Andini_Kunti Mulangsri; Mufrod Mufrod (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTBreadfruit leaves contain flavonoid compounds that can inhibit the growth of Staphylococcus aureus bacteria. Breadfruit leaf extract is practical and effective formulated in ointment preparations. The base combination of PEG 400 and PEG 4000 decreases the melting point of PEG 4000, so that it is compatible and can increase the penetration of drugs in the skin. The objective of this study to determine the breadfruit leaf extract ointment with a combination of PEG 400 and PEG 4000 bases as well as antibacterial activity against Staphylococcus aureus bacteria. Breadfruit leaf extract (BLE) was obtained by maceration with 70% ethanol. Salve preparations were made into III formulas with variations in base concentrations of PEG 400 and PEG 4000, namely (F1) 75%: 25%, (F2) 50%: 50%, (F3) 25%: 75%, using the fusion method. Antibacterial activity test used agar well diffusion method. Kruskal Wallis test and Mann Whitney test used for analyzed data from antibacterial activity test. The ointment of Breadfruit leaves extract showed the color of brown ointment, semi-solid form, distinctive aroma of breadfruit leave. All of three ointment formulas have antibacterial activity indicated by the formation of inhibitory zones around the well. All of three ointment formulas have significant differences which means the combination of PEG 400 and PEG 4000 can affect antibacterial activity of BLE ointment. The higher of the concentration PEG 4000 compared PEG 400 caused inhibiton zone become smaller that means the potency of antibacterial decreased. The formula has the greatest antibacterial activity in the FI is 8,02mm.Keywords: breadfruit leaves, ointment, PEG 400 and PEG 4000, antibacterial